Bahasa Inggris - Ari Sentana, Anak Agung Bagus; Istiqomah, Nurul; Giovani, Evelin (Musamus Journal of Language and Literature, 2024)
This study aims to analyze the motivation of the main character, Tom Sawyer, as depicted in the novel The Adventures of Tom Sawyer, written by Mark Twain in 1876 and first published in 1884 by The American Publishing Company. The theory used in this research is the motivation theory by Ryan and Deci, which classifies motivation into two categories, extrinsic motivation and intrinsic motivation. The method used in this study is the descriptive qualitative method, which is suitable for literary analysis as it involves examining and describing written texts or documents using the theory of motivation. Every individual has different dreams and needs, and this is reflected in the various motivations shown by Tom Sawyer in the novel. Based on the analysis, it is found that Tom Sawyer's actions and behaviors are driven by intrinsic motivation, such as adventure and curiosity, pleasure and entertainment, and the desire to test boundaries, as well as extrinsic motivation, including recognition and praise, love and acceptance, avoidance of punishment, and social status. Both types of motivation are rooted in the fulfillment of basic needs: autonomy, competence, and relatedness.